The use of collagen biomaterial in oral cancer: a systematic review - Mohamed Halim, Muhammad Lutfi; Mohd Zayi, Nora Azirah; Mohamad, Mohd Yusof; Arzmi, Mohd Hafiz (2019)
Introduction: Oral cancer is the sixth most common malignancy in the world. It is a major concern in Southeast Asia primarily due to betel quid chewing, smoking, and alcohol consumption. In Malaysia, oral cancer related cases accounts for 1.55% of the cause of deaths. Despite recent advances in cancer diagnoses and therapies, the survival rate of oral cancer patients only reached 50% in the last few decades. Tissue engineering (TE) principles may provide new technology platforms to study mechanisms of angiogenesis and tumour cell growth as well as potentially tumour cell spreading in cancer research. The use of biomaterial, appropriate cell source and proper signalling molecules are vital components of TE. Collagen biomaterial are widely used scaffold or membrane in oral application. Nevertheless, no review has been performed on the its usage for the study of oral cancer. This study aimed to systematically review the use of collagen scaffold in oral cancer application. Methods: Research articles were searched using Scopus, Pubmed and Web of Science (WOS) databases. The keywords were limited to “collagen membrane OR collagen scaffold” AND “oral cancer”. Results: Initial search yielded 61 papers (Scopus:37, Pubmed: 12, WOS: 12). Further scrutinization of the papers based on the inclusion criteria resulted total of 3 papers. Two of the papers used collagen membrane for regeneration of oral mucosal defect and increment of alveolar ridge height post-surgery. The remaining paper utilize collagen biomaterial as scaffold for the culture of adenoid cystic carcinoma (ACC) cells. All papers reported significant role of collagen biomaterial in terms of tissue formation, healing scaffold and cellular proliferation. Conclusion: Collagen utilization as biomaterial offers potential use for regeneration of oral related structures as well providing useful model for therapeutics anti-cancer research